INDONESIAN CONSTITUTIONAL GUARANTEES AGAINST DISCRIMINATORY TREATMENT: AN EMPIRICAL STUDY - Manitra, Ramalina Ranaivo Mikea; Prabandari, Adya Paramita (Diponegoro Law Review, 2024)
The right to be free and protected from discriminatory treatment is universal. Such right is incorporated into the 1945 Constitution of the Republic of Indonesia. This paper examines the perception of international students (30 respondents) in Indonesia regarding the discriminatory treatment they have experienced and the effort of the Indonesian Government to address such issue in educational institutions. The study focuses on the operation of positive law, particularly Article 28I Paragraph (2) and Paragraph (4) of the 1945 Constitution. The method used was empirical legal research, combined with statutory and sociological approaches, utilizing primary data (from questionnaires) and secondary data. The analysis of questionnaire output reveals a concerning reality of discriminatory treatment in various forms experienced by the respondents. A significant percentage of them experience discriminatory treatment and perceive a lack of effective measures to address and prevent such discrimination in educational institutions. Recommendations are made to bridge the gap between constitutional guarantees and the actual experiences of international students: Indonesian government should strengthen the implementation of anti-discrimination laws, foster inclusive environments in educational institutions, and enhance government efforts through better monitoring, complaint systems, and legal remedies for victims, in alignment with constitutional guarantee.